Improving quality of teaching and child development: A randomised controlled trial of the leadership for learning intervention in preschools - Iram Siraj; Edward Melhuish; Steven J. Howard; Cathrine Neilsen-Hewett; Denise Kingston; Marc De Rosnay; Runke Huang; Julian Gardiner; Betty Luu (Frontiers in Psychology, 2023)
IntroductionSubstantial research indicates that high quality early childhood education and care (ECEC) confers a wide range of benefits for children, yet quality in ECEC remains inconsistent. Given the variability in training and qualifications, one strategy for improving ECEC quality is in-service professional development (PD).MethodsThe current study evaluated an evidence-based in-service PD programme, Leadership for Learning, via a cluster randomised controlled trial involving 83 ECEC services and 1,346 children in their final year of pre-school.ResultsResults indicated significant improvements in teaching quality across treatment centres and child development outcomes in language, numeracy and social-emotional development.DiscussionThis study provides strong support for making evidence-informed PD routinely available for ECEC practitioners.